Pengembangan Kurikulum Pendidikan Teknik Informatika dan Komputer di Era Revolusi Industri 4.0 - Suryani, Karmila; Jalinus, Nizwardi; Khairudin, Khairudin (Efektor, 2019)
This paper analyzes the steps of curriculum change that must be carried out at The Information and Computer Engineering Education(ICCE) study program of Bung Hatta University, to realize standards of graduate competency as contained in the formulation of Learning Outcomes (LO). Especially in the face of the Industrial Revolution(IR) 4.0 era with three additional literacy, demanding changes in content by maintaining a balance between the development of spiritual and social attitudes, creativity, independence, cooperation with intellectual and psychomotor abilities. Some recommendations that are immediately fulfilled are 1) Re-improving the profile of graduates in accordance with the demands of the labor market and appropriate scientific progress IR 4.0, 2). Constructing LO and LO-Courses, 3) Rearranging materials, strategies, evaluation techniques that are in accordance with the HE curriculum guidelines, 4) Accommodating differences in individual abilities and disabilities 5). Conducting workshops for lecturers in making Semester Learning Plan(SLP) in accordance with the demands of IR. 4.0.